Strategi Penjualan Jagung Dan Kacang Rebus Di Kota Tebing Tinggi - Silitonga, Dwi; Rusmewahni, Rusmewahni (Management And Business Progress, 2023)
The large number of MSME people increases competition in the market, especially for small or micro business owners. Therefore, several changes are needed from business people, one of which is implementing certain strategies to market their products. A business located in Kampung Bicara area of Tebing Tinggi City sells sweet corn and boiled peanuts. To be able to continue to survive and develop in the Tebing Tinggi, of course, this business requires a good business marketing strategy. The purpose of this activity is to find out the obstacles faced and what solutions must be implemented in maintaining the business of selling corn and boiled peanuts so that it continues to grow. The obstacle found that a large number of business people of boiled corn and peanut had more interesting innovations to attract customers. The solution to this problem is to add a variety of flavors, spices or create new and unique preparations. Business people must also provide good service and be responsive to customers. In addition, by making promotional strategies through social media, such as Whatsapp, Facebook, Tiktok, or other types of social media by uploading photos of their products on social media so that they can arouse appetite and attract customer attention.